Novel Phialophora species from leaf-cutting ants (tribe Attini) - Attili-Angelis, D. [UNESP]; Duarte, A. P. M. [UNESP]; Pagnocca, F. C. [UNESP]; Nagamoto, N. S. [UNESP]; Vries, M. de; Stielow, J. B.; Hoog, G. S. de (Springer, 2014)
Ants in the tribe Attini (Hymenoptera, Formicidae) maintain a 50 million-year-old lifestyle of co-evolution with symbiotic basidiomycetous fungi which they cultivate as essential source of nutrition. However, other microorganisms have been reported from ant habitats indicating a higher diversity of consistently associated species than established to date. Recently, black yeast-like fungi have been reported as a possible symbiont, like a competitor of the actinomycete bacteria that grow in the integument of the insects. During the mating season, gynes of Atta capiguara and A. laevigata were collected from nests located in Botucatu, SP, Brazil and sampled using flotation technique. Phylogenetic analysis based on ITS, partial 28S (LSU) and beta-tubulin sequences revealed the occurrence of two novel species of Phialophora among the melanized fungi isolated.
Keywords: Black yeasts; Chaetothyriales; Gynes; Phialophora; Cyphellophora; Atta; Ant cuticle; Neotropical fungal ecology